tert-Butylation of p-cresol over WOx/ZrO2 solid acid catalysts - Sarish, S.; Devassy, Biju M.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A - Chemical, 2005)
The tert-butylation of p-cresol with tert-butanol was carried out over WO3/ZrO2 catalysts under flow conditions, The catalysts were prepared by wet impregnation method using zirconium oxyhydroxide and ammonium metatungstate. Catalysts with different WO3 loading (5-30 wt.%) were prepared and calcined at 800 degrees C and catalyst with 15% WO,, was calcined from 600 to 900 C. The catalysts were characterized by surface area, XRD, FTIR and TEM. The catalyst 15% WO3/ZrO2 calcined at 800 degrees C found to be the most active in the reaction. The effect of temperature, space velocity and molar ratio of the reactants on the conversion of p-cresol and products selectivities were studied. Under the optimized reaction conditions of 130 degrees C, tert-butanol/p-cresol molar ratio of 3 and flow rate of 10 ml h(-1). p-cresol conversion was 69.8% with selectivity to 2-tert-butyl-p-cresol 92.4%, 2,6-di-tert-butyl-p-cresol 6.3% and p-cresol tert-butyl ether 1.3%. The catalytic activity is compared with sulfated zirconia, USY, H beta zeolites and montmorillonite K-10 under the optimized reaction conditions The activity of sulfated zirconia is lower than that of 15% WO3/ZrO2 catalyst calcined at 800 C and other catalysts showed very low activity, (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: p-Cresol; tert-butylation; tungsten oxide; Zirconia